Spin-Dependent Transport Properties of a Phenylene Rotor Bridging Carbon Chains Between Graphene Electrodes (Communications in Computational Physics, 2018)
We study the spin-dependent electron transport by using ab initio calculationsfor a molecular junction consisting of a phenylene capped by two carbon chainswhich is sandwiched between two zigzag-edged graphene nanoribbon (ZGNR) electrodesmodulated by external magnetic fields or ferromagnets. It is shown that thespin-charge transport can be adjusted by the phenylene rotation angles in respect toZGNR electrodes and spin orientation in electrodes. Specifically, we demonstrate thatthe proposed molecular device exhibits switching, (dual) spin-filtering, rectifying, negativedifferential resistance (NDR) effects. Interestingly, when the phenylene rotationangle is θ=60◦, the maximum value of the peak-to-valley ratio of NDR is up to 26, thespin-resolved rectification ratio can reach up to 2.47×104, and the spin filtering efficiency reaches up to 100%. The physical mechanisms of these effects are analyzed viathe spin-resolved transmission spectrum associated with local density of states (LDOS)and molecular projected self-consistent Hamiltonian (MPSH) eigenvalues.
Keywords: ab initio calculations; spin-dependent transport; all-carbon molecular device.